The Effect of Power and Internet Challenges on the Productivity of Small Enterprises in Southeast Asia: An Empirical Analysis - Leo Delaric Manansala; Eric Abuso Vargas (International Journal of Applied Business and International Management, 2025)
This study examines the effect of power shortages and internet interruptions on the productivity of small retail firms in Southeast Asia, specifically in Indonesia, the Philippines, and Vietnam. Using data from the 2015 and 2023 World Bank Enterprise Surveys, the research investigates how these disruptions affect firm output, with a focus on small enterprises, a sector often overlooked in existing literature. Power shortages have been shown to hinder productivity, but the effect varies by country, with regional and national contexts influencing the outcomes. This study incorporates internet interruptions as a newly considered variable in the 2023 data, adding a modern perspective on how digital infrastructure challenges impact small businesses. Using the Fixed Effects Model, Random Effects Model, and Ordinary Least Squares regression techniques, the research identifies significant effects of power shortages on productivity, particularly in Indonesia and Vietnam. However, internet interruptions did not show a statistically significant impact across the regions studied. The findings suggest that small retail firms may be less reliant on stable internet access compared to sectors that are more digitally intensive. The study highlights the importance of tailored, localized strategies to mitigate disruptions and calls for future research to explore contextual factors and adaptive strategies that affect productivity in the face of infrastructure challenges.